Design of Experiments for Reactivity Ratio Estimation in Multicomponent Polymerizations Using the Error‐In‐Variables Approach. Issue 5 (6th June 2013) - Kazemi, Niousha; Duever, Thomas A.; Penlidis, Alexander
<x xml:space="preserve">Abstract</x> Model‐based design of experiments using the error‐in‐variables model (EVM) is explored. The fundamental differences between DOE in the traditional nonlinear regression versus the EVM context are discussed, and it is pointed out that for cases where there are errors in all variables, using the EVM design criterion is the only appropriate approach. In addition, the implementation of the EVM design criterion and its characteristics for both initial and sequential design schemes are discussed. The main application is the implementation of the EVM criterion to design optimal trials for reliable estimating reactivity ratios for typical copolymerization systems, along with prescriptions for the practitioner.<inline-graphic xlink:href="ark:/27927/pgg224ph73k" content-type="mats201200085-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />